Surgical factors influencing local relapse and outcome in the treatment of unilateral nephroblastoma - Meier, Clemens-Magnus; Fuchs, Jörg; von Schweinitz, Dietrich; Stein, Raimund; Wagenpfeil, Stefan; Kager, Leo; Schenk, Jens-Peter; Vokuhl, Christian; Melchior, Patrick; Welter, Nils; Furtwängler, Rhoikos; Graf, Norbert (Annals of surgery, 2023)
Objective: - This study aims to identify factors associated with the occurrence of local relapse (LR) after treatment for unilateral nephroblastoma. - Background: - Despite the fact that LR is rare (~5%) its adverse impact on the need for relapse treatment and outcome (40%-80% overall survival) cannot be neglected. Identifying the causative factors may improve initial treatment to achieve better local control. - Methods: - altogether 2386 patients with unilateral nephroblastoma prospectively enrolled over a period of 32 years (1989-2020) by the German Society for Pediatric Oncology and Hematology (SIOP-9/GPOH, SIOP-93-01/GPOH and SIOP-2001/GPOH) were retrospectively analyzed. Hazard ratios (HR) of LR were calculated for sex, age, size, local staging, histology, type of removal, rupture, lymph node (LN) removal using univariate and multivariate Cox models. - Results: - Age >48 months, tumor volume >500 mL, histology and LN extent of removal were identified as significant risk factors for LR [HR: 1.68, P=0.018, confidence interval (CI): 1.09-2.58; HR: 1.84, P=0.015, CI: 1.13-3.00; HR: 3.19, P<0.001, CI: 2.03-5.00; HR: 2.26, P=0.002, CI: 1.36-3.576]. LR occur significantly more often in Stage I and II, even if no LN are removed. The risk of metastases is significantly increased after local recurrence (HR: 11.5, P<0.001, CI: 7.11-18.60). LR is associated with a subsequent 18.79-fold increased risk of death (HR: 18.79, P<0.001, CI: 2.07-5.28). - Conclusions: - Several factors are responsible for the occurrence of LR. Surgical ones, like LN sampling allow further reduction of LR and consequently a better outcome of patients with unilateral nephroblastoma.